Analisis Makna Simbolik Dan Makna Komunikasi Non Verbal Tradisi Adat Mangongkal Holi Dalam Suku Batak Toba Di Sumatera Utara - Putri Dinda; Sri Rejeki; Vira Ningsih; Weand Nabilla; Frinawaty Lestarina Barus; Emasta Evayanti Simanjuntak (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2023)
The Mangongkal Holi tradition which is carried out at each event makes the writer interested in researching it because in its implementation there are symbols and behaviors/activities that are interconnected and have their own meaning. What is the importance of the Mangongkal Holi tradition for the Toba Batak people so that this tradition must be carried out. This study uses descriptive analysis with qualitative research, which emphasizes the perspectives, ways of life, tastes or expressions of emotions and beliefs from the people studied regarding the problems studied which are also data. In this study the authors used a descriptive research method with a qualitative method. Therefore, the research subjects were traditional leaders, families who carry out the Mangongkal Holi ceremony, and local residents in North Sumatra. And the object of this research is the symbolic meaning of the Mangongkal Holi ceremony for the Toba Batak people in North Sumatra. Purposive sampling technique used to take informants.